Self-Assembly and Ordering of C-60 on the WO2/W(110) Surface - SHVETS, IGOR; MURPHY, BARRY (My University, 2011)
The growth and ordering of C60 molecules on the WO2/W(110) surface have been studied by low-temperature scanning tunnelling microscopy and spectroscopy (STM and STS), low-energy electron diffraction (LEED) and density functional theory (DFT) calculations. The results indicate the growth of a well-ordered C60 layer on the WO2/W(110) surface in which the molecules form a close-packed hexagonal structure with a unit cell parameter equal to 0.95 nm. The nucleation of the C60 layer starts at the substrate?s inner step edges. Low-temperature STM of C60 molecules performed at 78 K demonstrates wellresolved molecular orbitals within individual molecules. In the C60 monolayer on the WO2/W(110) surface, the molecules are aligned in one direction due to intermolecular interaction, as shown by the ordered molecular orbitals of individual C60. STS data obtained from the C60 monolayer on the WO2/W(110) surface are in good agreement with DFT calculations.
PUBLISHED
Keywords: C-60; self-assembly; ordering; WO2/W(110); Nanoscience & Materials